Development Strategy for Seaweed Agroindustry on Household Scale in Mataram City - Purnamasari, Ratih; Sudjatmiko, Dwi Praptomo; Suparmin, (International Journal of Scientific Research and Management (IJSRM), 2024)
The research objectives are (1) Analyzing alternative strategies for developing agro-industry made from seaweed in Mataram City; and (2) Analyzing the strategic options that are prioritized in the development of seaweed agro-industry in Mataram City. The research method uses descriptive methods. Determining the research location was carried out using the Purposive Sampling technique. The main respondents in the research were seaweed agro-industry entrepreneurs. To strengthen data related to product quality and price instruments, data was added by interviewing buyers/consumers as additional respondents, so the assessment was more objective. Producer respondents were determined using the census method, while consumer respondents were determined using the Accidental Sampling method. The results of the research show (1) Alternative development strategies using SWOT, obtained by micro-businesses in quadrant Ⅲ (WO Strategy) include utilizing coaching for access to capital, modern technology, good packaging, expanding the market through social media, increasing the number of human resources, and promotions to overcome less strategic location. For small businesses in quadrant Ⅰ (SO Strategy) by utilizing experience and business permits to create employment opportunities, process agricultural products, promote quality products without preservatives, and use guidance from related agencies, (2) QSPM matrix analysis produces priority strategies for Micro business is expanding the market and promoting through social media to meet high product demand, while for small business it is increasing the added value of products with available raw materials and utilizing guidance from related agencies.